Elementary School Student Learning Independence Analyst during the Covid-19 Pandemic - Kisman Kisman; A. Hari Witono; Moh. Irawan Zain (IKIP Mataram, 2021)
Independent learning is an important element in learning. Independent learning is defined as a learning process within a person in achieving certain goals that are required to be active individually or not to depend on others, including teachers. This study aims to find out how independent student learning is during the Covid-19 pandemic and the factors causing difficulties in student learning independence during the Covid-19 pandemic class V SD Negeri 46 Mataram. The research approach used is descriptive qualitative research. The data collection instruments used interview questionnaires, observation sheets, and documentation studies. The data analysis technique used is data reduction, data presentation, conclusion or verification. The results show that the learning independence experienced by class V students includes: (1) aspects of having self-confidence reaching an average percentage of 50.3%, (2) aspects in making decisions reached an average percentage of 38.6%, (3) responsible aspects reached an average percentage of 50%, (4) aspects of having a competitive desire to advance reached an average percentage of 44.6%, (5) the discipline aspect reached an average percentage of 41.5%. Then the student's learning independence factor in terms of self-confidence, the average percentage is 44.33%. Then the student's learning independence factor in a decision, the average percentage is 36.66%. Then the independent learning factor of students in terms of responsibility, the average percentage is 45.75%. Then the student's learning independence factor in terms of the desire to compete to advance, the average percentage is 38.66%. Then the student's learning independence factor in terms of discipline, the average percentage is 50%